Pengaruh Penggunaan Teknik Mind Mapping Berbantuan Mind Meister terhadap Kemampuan Menceritakan Kembali Isi Teks Narasi Siswa Kelas VII SMP Negeri 1 Parbuluan - Yoyuti Sonata Capah (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This study, utilizing MindMeister, aims to examine the impact of using the mind mapping technique on the ability of 7th-grade students at SMP Negeri 1 Parbuluan to retell the content of a narrative text they have read. The research population consisted of 172 7th-grade students, with a sample size of 56 students divided into two groups: a control class and an experimental class, each comprising 28 students. The research employed a quantitative method with a true experimental design. The research instrument was a performance test, and the data were analyzed using a t-test. Based on the results, the average score of students’ ability to narrate the content of a narrative text using the close reading technique was 62.21, with a standard deviation of 6.33, which falls into the “poor” category. Meanwhile, the students’ ability to retell the narrative text using the mind mapping technique with the assistance of MindMeister was 80.07, categorized as “good,” with a standard deviation of 5.48. The data indicated an improvement in the average scores between the control class, which used the intensive reading technique, and the experimental class, which applied the mind mapping technique. Through hypothesis testing, it was found that Thitung > Ttabel, thus rejecting H0 and accepting H1. This means that the use of the mind mapping technique with the help of MindMeister positively influences the ability of 7th-grade students at SMP Negeri 1 Parbuluan to retell narrative texts.